Pengaruh Persepsi Risiko terhadap Intensi Menggunakan E-wallet di Jabodetabek dengan Mediasi Persepsi Kegunaan dan Persepsi Kemudahan Penggunaan - Laksmidewi, Dwinita; Kumara, Kairos (Journal of Business Studies and Management Review, 2024)
This study aims to determine the influence of Perceived Risk, Perceived Usefulness and Perceived Ease of Use on Intention to use and to see the role of Perceived Usefulness and Perceived Ease of Use as Mediating variables. The researcher used purposive sampling to 125 e-wallet user respondents. This study used the Partial Least Square Structural Equation Model (PLS-SEM). The Perceived Risk variable was analyzed using outer loading first order to determine the role of its dimensions consisting of Privacy risk, financial risk, Time risk, psychological risk, and security risk. The results of the study showed that Perceived Risk had a significant negative effect on Perceived Usefulness and Perceived Ease of Use. The study also showed that the Perceived Usefulness and Perceived Ease of Use variables had a positive and significant effect on intention to use E-wallet. Furthermore, Perceived Usefulness and Perceived Ease of Use significantly mediated the influence of perceived risk on intention to use e-wallet.